Raais Character Ethic Framework: Integrating The Civilisational Values And Principles In The Islamic Gifted Education Model - Zulkarnin Zakaria; Ahmad Bazli Ahmad Hilmi; Zamrus Mohd Ali; Tg Ainul Farha Tg Abdul Rahman; Rossidi Usop; Nurdalila A’wani Abdul Aziz; Myra Aidrin Mohd Ali (Universiti Sains Islam Malaysia, 2024)
‘Abqari Journal. Volume 31, Issue 2 Page ( 48–67)